Optimizing Market Segmentation for Industrial Water Sector in Indonesia: A Strategic Approach - Ruvi, Mohammad (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The industrial water sector in Indonesia is a critical component of the nation's economic development, yet it faces significant challenges in market segmentation and targeting. This study explores the potential of optimizing market segmentation strategies to enhance the efficiency and effectiveness of water management solutions in the industrial sector. By employing a mixed-methods approach, including literature review, case study analysis, and expert interviews, this research identifies key factors influencing market segmentation, such as industry-specific needs, regulatory frameworks, and technological advancements. The findings suggest that tailored segmentation strategies, combined with data-driven decision-making, can significantly improve market penetration and customer satisfaction. This study provides actionable insights for policymakers, industry stakeholders, and marketers aiming to optimize market segmentation in the industrial water sector.